Behartiging van het onderwijs in coronatijd in Nederland en Zuid-Afrika: een vergelijkende studie - Broer, Nicolaas A. (HTS teologiese studies, 2022)
Managing education during the pandemic in the Netherlands and South Africa: A comparative study. Optimism has reigned supreme for a long time regarding the potential of education (schooling) to address the many societal ailments that humankind has had to deal with. The outbreak of the COVID-19 pandemic in March 2020 shifted all such aspirations to the back-burner. Now, after just more than a year after the initial outbreak of the pandemic, the question can be raised whether those who managed the pandemic in the educational context followed the correct policies and instituted the correct (ethical, moral) measures in combatting the pandemic. This comparison between the situation in the Netherlands and South Africa reveals that although the role-players in both countries had a good understanding of the situation and of their duties in such conditions, they tended to treat education as just another facet of society, thereby demonstrating a lack of empathy with the unique demands of education (schooling).Contribution: In this article, the authors investigate the governance performance of two different countries during the first year of the COVID-19 pandemic concerning education and judge that performance based on a Biblically driven ethical-moral-pedagogical framework.